2021
DOI: 10.30572/2018/kje/100309
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Polyethylene Matrix Composites Using Coconut Shell and Cow Bone Particulates

Abstract: Utilisation of particles of coconut shell and cow bone as reinforcing materials for the production of low density hybrid polyethylene matrix composites by stir casting method was carried out. 50 µm coconut shell and 50 µm cow bone particulates in different proportions (5-25 wt. %) were mixed with polyethylene and the microstructural, physical and mechanical characterisations were determined using standardised methods. The hybrid composite exhibited desirable properties in terms of water absorption (0.3 %) indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
5
2
0
Order By: Relevance
“…The decrease observed in the flexural strength could be due to poor interfacial bonding between the particles and the polyester matrix as a result of inhomogeneity and agglomeration of the particles. This agrees with the submission/report of Mechtali et al (2015), Rufai et al (2015) and Durowaye et al (2019).…”
Section: Flexural Strengthsupporting
confidence: 92%
See 3 more Smart Citations
“…The decrease observed in the flexural strength could be due to poor interfacial bonding between the particles and the polyester matrix as a result of inhomogeneity and agglomeration of the particles. This agrees with the submission/report of Mechtali et al (2015), Rufai et al (2015) and Durowaye et al (2019).…”
Section: Flexural Strengthsupporting
confidence: 92%
“…This is higher than that of the reinforced samples. The reduction in the impact energy could be due to agglomeration of the particulates in the resin matrix which agrees with the report of Mechtali et al (2015), Rufai et al (2015) and Durowaye et al (2019).…”
Section: Impact Energysupporting
confidence: 91%
See 2 more Smart Citations
“…From the table, it was observed that the calcined cow bone contained phosphorus, while the kaolin sample was made up of silicon and aluminum. The presence of phosphorus in calcined cow bone was observed by Durowaye et al, 34 while the presence of silicon and aluminum in kaolin was also observed by Ahmed and Selim 62 . The polystyrene resin, as shown in the table, was primarily made up of carbon (98%) and silicon (1.82%).…”
Section: Resultsmentioning
confidence: 65%